Targeting lncRNAs of colorectal cancers with natural products - Sung, Woo Jung; Hong, Jaewoo (Frontiers in Pharmacology, 2023)
Noncoding RNA (ncRNA) is one of the functional classes of RNA that has a regulatory role in various cellular processes, such as modulation of disease onset, progression, and prognosis. ncRNAs, such as microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs), have been actively studied in recent years. The change in ncRNA levels is being actively studied in numerous human diseases, especially auto-immune disorders and cancers; however, targeting and regulating ncRNA with natural products to cure cancer has not been fully established. Recently many groups reported the relationship between ncRNA and natural products showing promising effects to serve as additional therapeutic approaches to cure cancers. This mini-review summarizes the aspects of lncRNAs related to cancer biology focusing on colorectal cancers that natural products can target.